The “Vernacular” in Culture: Common Language of Local Experience - Volodina, Alexandra V. (Actual Problems of Theory and History of Art, 2025)
This paper examines the theoretical potential of the various approaches to the studies of the “vernacular” in art and culture, which help to analyze how the seemingly universal language of mass and mainstream culture is interpreted in local everyday experience. The author traces the history of the term “vernacular” as it expanded from mostly descriptive (being used to characterize buildings created without a professional architect) to a more critical approach. This opened new possibilities to study the accidental, fluid, and “mediating” ways of practicing and perceiving the art. Such transformation of the term was initiated by scholars D. Upton, P. Oliver, E. Hutchinson, and M. Hansen. Vernaculars are reflexive images able to theorize about local cultural experience, and the research tends to focus not on the vernacular art per se but on the vernacular in art: i.e. not the formal specificity of the artifact but the relations with the cultural forms and the site-specific lived experience. This theoretical frame of the “vernacular” provides us with two important aspects of cultural practices: the ability to translate and combine different modes of contemporaneity and the performativity of the ordinary. The final part of the paper is dedicated to the research of the environments and assemblages made by self-taught artists. The author attempts to conceptualize the “vernacular” in these assemblages and to show how they vernacularize the very notion of the work of art.
Keywords: vernacular; mass culture; self-taught art; environmental art; artist-built environment; assemblage; performativity; Hansen; Williams; Upton